Alteration of long non-coding RNAs and mRNAs expression profiles by compound heterozygous ASXL3 mutations in the mouse brain. Issue 1 (1st January 2021) - Zhang, Songhui; Fu, Fang; Zhen, Li; Li, Ru; Liao, Can
ABSTRACT: Compound mutations in the additional sex combs-like 3 (ASXL3) gene greatly impact the expression of long non-coding RNAs (lncRNAs) and messenger RNAs (mRNAs) in mouse myocardial tissues. Little is known about ASXL3 mutation effects on lncRNAs and mRNAs expression in the cerebrum and cerebellum. This study aims to clarify this point using quantitative real-time polymerase chain reaction and Western blotting. Transcriptome analysis based on RNA-seq followed by bioinformatics analysis were used to compare lncRNA and mRNA expression profiles. Cell proliferation, cell cycle progression, and apoptosis were evaluated after silencing of ASXL3 expression using the 3-(4, 5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4- sulfophenyl)-2 H-tetrazolium method and flow cytometry. Results showed that ASXL3 gene expression was decreased in the cerebrum and cerebellum of mice with ASXL3 P723R*P1817A mutations. We identified 319 lncRNAs and 252 mRNAs differentially expressed in the cerebrum of ASXL3 P723R*P1817A mutant mice. In the cerebellum of ASXL3 P723R*P1817A mutant mice, 5330 lncRNAs and 2204 mRNAs were differentially expressed. Differentially expressed lncRNAs and mRNAs were widely distributed across the mouse genome and were associated with various biological processes and pathways. ASXL3 silencing by siRNA transfection affected the proliferation, cell cycle progression, and apoptosis of neural cells. Therefore, the ASXL3 P723R*P1817A mutations greatly modify the lncRNA and mRNA expression profiles in the mouse cerebrum and cerebellum.